Similar but different: High prevalence of synesthesia in autonomous sensory meridian response (ASMR) - Poerio, Giulia L.; Ueda, Manami; Kondo, Hirohito M. (Frontiers in Psychology, 2022)
Autonomous Sensory Meridian Response (ASMR) is a complex sensory-emotional experience characterized by pleasant tingling sensations initiating at the scalp. ASMR is triggered in some people (called ASMR-responders) by stimuli including whispering, personal attention, and crisp sounds (termed ASMR triggers). Since its inception, ASMR has been likened to synesthesia, but convincing empirical data directly linking ASMR with synesthesia is lacking. In this study, we examined whether the prevalence of synesthesia is indeed significantly higher in ASMR-responders than non-responders. A sample of working adults and students (N = 648) were surveyed about their experience with ASMR and common types of synesthesia. The proportion of synesthetes who were classified as ASMR-responders was 52%, whereas 22% of ASMR-responders were also synesthetes. These results suggest that: (1) over half of those identifying as synesthetes also experience ASMR, and (2) that synesthesia is up to four times as common among ASMR-responders as among non-responders (22% vs. 5%). Findings also suggest a prevalence rate for ASMR of approximately 20%. Overall, the co-occurrence of ASMR and synesthesia lends empirical support to the idea that ASMR may be driven by synesthetic mechanisms, but future research would benefit from examining how ASMR and synesthesia are different, as well as similar.